An improved Chang cryptography scheme - XU Ming; YING Jing; CHEN Chun (浙江大学学报. 农业与生命科学版)
Digital signature and fault tolerance are two important issues in modern computer network communication. In most case, they are addressed and implemented separately. Recently, Chang proposed an integrated approach for both fault tolerance and digital signature in RSA, which can implement fault tolerance in processes of encrypting, transmission, decrypting and authentication. In this paper, we analyze some security faults which exist in Chang cryptography scheme, Then we propose an approach, which can be used to attack Chang scheme. Finally, we propose an improved Chang cryptography scheme, which provides perfect cryptography, fault tolerance, impossibility of being interpolated, impossibility of being retransmitted. and so on. The improved scheme embodies a new way of thinking for public key cryptography by integrated approach for fault tolerance and digital signature in RSA.